2021
DOI: 10.1111/1751-2980.12992
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of artificial intelligence‐assisted detection of esophageal cancer and neoplasms on endoscopic images: A systematic review and meta‐analysis

Abstract: To investigate systematically previous studies on the accuracy of artificial intelligence (AI)-assisted diagnostic models in detecting esophageal neoplasms on endoscopic images so as to provide scientific evidence for the effectiveness of these models.Methods: A literature search was conducted on the PubMed, EMBASE and Cochrane Library databases for studies on the AI-assisted detection of esophageal neoplasms on endoscopic images published up to December 2020. A bivariate mixed-effects regression model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…On the other hand, in this study, the performance of AI applied to real‐time videos was not statistically different from that on still images, and the performance of AI was similar to that of endoscopists. Additionally, a recent meta‐analysis reported that the inclusion of video clips in the training and validation data sets of AI models could achieve even higher performance than those including images alone 66 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in this study, the performance of AI applied to real‐time videos was not statistically different from that on still images, and the performance of AI was similar to that of endoscopists. Additionally, a recent meta‐analysis reported that the inclusion of video clips in the training and validation data sets of AI models could achieve even higher performance than those including images alone 66 …”
Section: Discussionmentioning
confidence: 99%
“…Zhang S.M. et al showed that the sensitivity of NBI for the diagnosis of esophageal squamous high-grade intraepithelial neoplasia varied greatly, reaching up to 100.0% by experienced endoscopists and only 69.0% by inexperienced physicians [ 20 ], indicating that the examination results of NBI are still influenced by the subjective factors of endoscopists. Because clinical upper DEN needs to be done by endoscopists, and diagnosis relies entirely on the endoscopist's visual interpretation and pathological biopsy, the essence is continuously accumulating experience to enhance accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang S.M. et al adopted a great number of samples to construct an AI model to learn 8,428 endoscopic images of patients with esophageal carcinoma, and the results showed that the sensitivity of AI diagnosis was 98.0% and the PPV was 40.0% [ 20 ]. Based on the features of AI learning, the PPV will continuously increase with the number of samples, and with the building of IOT data platform, the accuracy of AI also elevates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies trained CNNs to aid early detection in GEA, recently summarized in a meta-analysis that found superiority of applying DL for detection of Barrett’s esophagus [ 132 , 133 , 134 , 135 , 136 , 137 ]. Currently, clinical trials are already investigating its sensitivity and specificity, if applied in a clinical setting, with several studies showing DL models to identify early GEA [ 138 , 139 ].…”
Section: Machine Learning—basic Concepts Specific Applications and Future Directions In Geamentioning
confidence: 99%